Investigação criminal defensiva sob uma perspectiva criminológica : a possibilidade de (re)legitimação da seletividade do sistema processual penal brasileiro - Alves, Ana Carolina Sanhudo (2021)
The preliminary criminal investigation is an indispensable means to justice achievement in criminal procedure. It is known that the inequality of arms between the parties is a reality in Brazil. In order to solve this problem, one considers the possibility of including criminal defense investigation in Brazil’s legal framework. Therefore, the present dissertation is dedicated to this subject, where it aims to analyze it either from a criminological perspective and not only procedural. The objective is to examine whether this new investigative model can (re)legitimate selectivity in the criminal justice system. In this sense, one seeks to present the converging premises between Criminal Procedure and Criminology via the deductive method, going through the concept and the principles of the institute, the foreign legislation, its approach in Brazilian legislation, and its relationship with our elitist and stigmatizing criminal system. Such premises are brought to demonstrate the mishaps of the problem in question, leading us to the following conclusion: more than a legal framework that will promote legal security via criminal defense investigation, it urges that occurs either a transformation of the paradigm as a whole, sustained in a change of culture, perspective, and posture; as well as a reengineering of the criminal system.